Tantangan Universalitas Hak Asasi Manusia oleh Norma Domestik: Kebijakan Sudan Tidak Meratifikasi Convention on Elimination of All Forms of Discrimation Against Women - Enno Nuri Al Sarah; Mohamad Rosyidin (Journal of International Relations Diponegoro, 2020)
The Convention on Elimination of All Forms of Discrimination Against Women (CEDAW) in 1979 should be an international standard for regulating the universality of women's human rights throughout the world. However, in reality, CEDAW cannot be applied universally. This is because of the obstacles caused by the policies of several countries which decided not to ratify CEDAW. Sudan is one of the countries that chose to not ratify CEDAW as a basis for regulating the rights of men and women in their country. Previous research on Sudan's policy of not ratifying CEDAW tends to base its analysis through a feminist approach that focuses more on depictions of women's oppression. So that previous research, has not been able to find any concrete reasons regarding Sudan's decision of not ratifying CEDAW. This study uses constructivist theory that looks at state behavior based on non-material factors namely identity, norms, values and culture. The author believes that Sudan's policy of not ratifying CEDAW is caused by a mismatch between Sudan's domestic norms and universal norms under CEDAW.